(untitled) (Physical Education, Health and Social Sciences, 2025)
Objective: To find out comparative analysis of renal parameters in diabetic vs. non-diabetic patients. Methodology: The present study was conducted by reviewing the medical records of 140 renal patients who affected with and without diabetes at AL Noor Lab & digital X-Ray center from October 2024 to March 2025. Biochemical tests will include renal function tests (serum creatinine and blood urea) and glucose test (fasting, random and HbA1c) conducted to provide a comprehensive biochemical profile for each participant. Results: This research examined 126 blood samples for blood glucose, urea, and serum creatinine levels by employing standard biochemical techniques. The study population consisted of 51.6% males and 48.4% females in three age groups: 18-33, 34-49 and 50+ years. Statical analysis did not show any significant difference between normal and abnormal values of these parameters (p> 0.05).” Thus, hypothesis was rejected, which means the values were statistically insignificant. Conclusion: This research points out that diabetes negatively impacts renal functions, with creatinine levels deviating more than urea. Screening and glycemic control are essential in controlling diabetic nephropathy.